Thermal interaction between free convection and forced convection along a conducting plate embedded in a porous medium - Shu, Jian Jun (2012)
The article investigates the conjugate problem of free convection and forced convection along a conducting vertical plate separating two semi-infinite porous reservoirs maintained at different temperatures. The mean heat flux through the plate and the wall temperature distribution on the both sides of the plate are determined. The results show the effects of the resistance parameter Rt and free-to-forced-convection parameter Rt* on the mean heat transfer through the plate and on the wall temperatures of the both sides of the plate.